High-surface-area organic matrix tris(aza)pentacene supported platinum nanostructures as selective electrocatalyst for hydrogen oxidation/evolution reaction and suppressive for oxygen reduction reaction. (16th July 2021) - Vélez Santa, John Fredy; Menart, Svit; Bele, Marjan; Ruiz-Zepeda, Francisco; Jovanovič, Primož; Jovanovski, Vasko; Šala, Martin; Smiljanić, Milutin; Hodnik, Nejc
Abstract: Developing a Pt-based electrocatalytic material able to selectively catalyze hydrogen oxidation (HOR) while supressing oxygen reduction (ORR) is beneficial for durability of the fuel cells. Namely, degradation of carbon supported Pt particles is dramatically influenced by the unwanted ORR enrolling at the anode due to the air penetration during start-up/shut-down events. We present an organic matrix tris(aza)pentacene (TAP), which belongs to π-functional materials with ladder-like conjugated nitrogen-containing units, as the support for Pt to form a "smart" fuel cell anode able to selectively catalyze HOR and to suppress ORR. "Switching-on/off" of the composite material activity is provided by reversible reduction/oxidation of the TAP in the low potential region which provokes TAP - Hx TAP transition. Conductivity of the reduced Hx TAP enables supported Pt particles to effectively run HOR. In contrast, restricted conductivity of oxidized TAP analogue leads to the substantial drop in the ORR activity with respect to benchmark Pt/C catalyst. Graphical abstract: Pt/TAP composite is able to selectively catalyze HOR/HER and to suppress ORR via adjustment of the TAP conductivity. Such selective electrocatalysis is of great importance for durability of Pt-based fuel cells catalysts. Image 1 Highlights: Pt nanostructures were grafted on high surface area tris(aza)pentacene (TAP) matrix. Electrocatalytic activity of Pt/TAP composite for fuel cells reactions was studied. Pt/TAP showed similar HOR/HER activity with respect to benchmark Pt/C catalyst. ORR was significantly inhibited on Pt/TAP with respect to Pt/C. Selective catalysis is provided by potential dependent tuning of TAP conductivity.